Effect of Adding L-carnitine to High-Fat/Low-Protein Diets of Common Carp (Cyprinus carpio) and the Mechanism of Regulation of Fat and Protein Metabolism. (26th August 2022) - Luo, Wei; Chen, Pengyu; Zhang, Xiaoyang; Zhang, Yibo; Zhang, Shoudong; Sun, Kunpu; He, Feifei; Li, Luojia; Zhang, Ning; Xiong, Yinlin; Guo, Zhonggang; Du, Zongjun; et al.
Abstract : L-carnitine is a low molecular weight amino acid that plays an essential role in the oxidation of long-chain fatty acids. The regulatory effects and molecular mechanisms of L-carnitine on fat and protein metabolism in common carp ( Cyprinus carpio ) were investigated in this study. Common carp (n = 270 ) were randomly divided into three groups and fed either (1) common carp diet, (2) high-fat/low-protein diet, or (3) L-carnitine-high-fat/low-protein diet. Growth performance, plasma biochemistry, muscle composition, and ammonia excretion rate were all examined after 8 weeks. Additionally, each group's hepatopancreas was subjected to transcriptome analysis. The results showed that decreasing the feed protein/fat ratio resulted in a considerable increase in feed conversion ratio and a significant decrease in common carp-specific growth rate to 1.19 ± 0.02 P < 0.05 . Similarly, total plasma cholesterol sharply increased to 10.15 ± 2.07, while plasma urea nitrogen, muscle protein, and ammonia excretion levels dropped (P < 0.05 ). After adding L-carnitine to the high-fat/low-protein diet, it was found that the specific growth rate and protein content of the dorsal muscle increased significantly (P < 0.05 ). In contrast, the plasma total cholesterol and ammonia excretion rate decreased considerably at most time points after feeding (P < 0.05 ). The expression of genes in the hepatopancreas differed substantially between the different groups. Through GO analysis, it was demonstrated that L-carnitine increased the ability of fat decomposition by up-regulating the expression of cpt1 in the hepatopancreas and decreased the expression of fasn and elovl6 to reduce the production and extension of lipids. Simultaneously, mtor was more abundant in the hepatopancreas, implying that L-carnitine can increase protein synthesis. According to the findings, adding L-carnitine to high-fat/low-protein diets can stimulate growth by enhancing lipolysis and protein synthesis.